Locoregional ablative treatment of melanoma metastases. (1st October 2019) - Putzer, Daniel; Schullian, Peter; Bale, Reto
Abstract: Standard treatment of melanoma has been evolving rapidly over the last decade, with novel treatment approaches improving therapeutic outcome not only in early-stage disease but also in advanced stage metastatic patients. Despite the improvement of systemic therapy outcomes, the current treatment guidelines reflect the fact that locoregional treatment approaches can be beneficial in patients suffering from oligometastatic disease. Minimally invasive ablation techniques have been established as a therapeutic cornerstone in the management of liver tumors, representing a local curative, relatively low-risk procedure. Depending on the size and location of metastatic disease, and on the applied ablation and guidance technique, ablative treatment approaches are effective to treat metastases in solid organs such as the liver or lungs, effectively covering the entire tumor with the ablation zone including a safety margin (A0 ablation in analogy to R0 resection). However, only retrospective data and case reports on locoregional treatment of melanoma metastases are available up to now, and prospective evaluation of this therapeutic approach is warranted to evaluate the beneficial role in the treatment of metastatic melanoma patients.